Lectures on the Topology of 3-Manifolds an Introduction to the Casson Invariant. - Saveliev, Nikolai (De Gruyter, 2011)
This textbook, now in its second revised and extended edition, introduces the topology of 3- and 4-dimensional manifolds. It also considers new developments especially related to the Heegaard Floer and contact homology. The book is accessible to graduate students in mathematics and theoretical physics familiar with some elementary algebraic topology, including the fundamental group, basic homology theory, and Poincaré duality on manifolds.